Dural architecture of the cavernous sinus. Structure of the dura mater of the sellar region - R. N. Lunkova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
This work is devoted to the study of the topography of the cavernous sinus and the clinical and anatomical substantiation of neurosurgical operations. Aspects of the topography of the internal carotid artery, cavernous sinus, cranial nerves of the sellar and paraclinic regions, topography and structure of the dura mater on the skull base, dura mater duplicates, cerebellar nave ligament, meningeal membranes (cerebral base cistern membrane, proximal carotid ring carotid membrane) and carotid rings are revealed. The work contains a large number of topograms and diagrams based on scientific literature data, as well as the author's own observations.